On privacy in information technologies: a window without curtains? - Mormontoy Pérez, Julio Jesús (2024)
The limited regulatory framework, insufficient jurisprudential development, and sparse doctrinal terrain concerning the violation of individuals' private information in the age of technological advancement have worryingly encroached upon the exclusive space of human beings. In the past, only those who deemed it important could share information with people in their environment through various platforms. However, today's reality is quite the opposite, as a wide range of computer science knowledge, including the use of Artificial Intelligence, now involves handling vast amounts of informative data from many individuals. This may also be considered a serious threat, leading to the creation and spread of intrusive digital environments in which individuals, companies, or states aim to monitor, analyze, predict, and even manipulate outcomes and human behavior, ultimately undermining the rights of others on an immeasurable scale. Therefore, this work is an attempt to describe and offer an analysis of the doctrinal foundations currently being conducted on information technologies, aiming to approach the understanding of their doctrinal core.